Toward a new generation of electrically controllable hygromorphic soft actuators - Taccola, Silvia (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.